Personal Knowledge: Towards a Post-Critical Philosophy - Polanyi, Michael 1891-1976 (Chicago, IL University of Chicago Press, 1974)
In this work the distinguished physical chemist and philosopher, Michael Polanyi, demonstrates that the scientist's personal participation in his knowledge, in both its discovery and its validation, is an indispensable part of science itself. Even in the exact sciences, "knowing" is an art, of which the skill of the knower, guided by his personal commitment and his passionate sense of increasing contact with reality, is a logically necessary part. In the biological and social sciences this becomes even more evident.The tendency to make knowledge impersonal in our culture has split fact from value, science from humanity. Polanyi wishes to substitute for the objective, impersonal ideal of scientific detachment an alternative ideal which gives attention to the personal involvement of the knower in all acts of understanding. His book should help to restore science to its rightful place in an integrated culture, as part of the whole person's continuing endeavor to make sense of the totality of his experience. In honor of this work and his The Study of Man Polanyi was presented with the Lecomte de Noüy Award for 1959.
Keywords: 20th Century (1901-2000); Philosophy